Lactic Acid Fermentation of Arabinoxylan From Nejayote by Streptococcus infantarius ssp. infantarius 25124 Isolated From Pozol - Cooper-Bribiesca, Barbara; Navarro-Ocaña, Arturo; Díaz-Ruiz, Gloria; Aguilar-Osorio, Guillermo; Rodríguez-Sanoja, Romina; Wacher, Carmen (Frontiers in Microbiology, 2018)
Streptococcus infantarius ssp. infantarius 25124 (Sii-25124) is a lactic acid bacterium (LAB) isolated from pozol, a refreshing beverage prepared by suspending fermented nixtamal (a thermal and alkali-treated maize dough) in water. Although Lactobacillus are the predominant strains in fermented doughs, such as sourdoughs, and non-nixtamalized fermented maize foods, the pozol microbiota is markedly different. This may be the result of the nixtamalization process, which could act as a selective force of some strains.Sii-25124 has been reported as the main amylolytic LAB in pozol; starch is the primary carbon source on nixtamal since monosaccharides and disaccharides are lost during nixtamalization; however, non-amylolytic LAB counts are higher than amylolytic LAB in pozol after 24-h fermentation suggesting that another carbon source is being used by the former bacteria.Hemicellulose (arabinoxylan in maize) becomes available via nixtamalization and is subsequently metabolized by LAB. The aim of this work was to determine whether this bacterium is able to use arabinoxylan as the only carbon source in a defined medium containing arabinoxylan extracted from either nejayote (wash water produced during nixtamal preparation), or beechwood xylan. Xylanase activity in the presence of nejayote arabinoxylan (135.8 ± 48.7 IU/mg protein) was higher than that of beechwood (62.5± 19.8 IU/mg protein). Other enzymatic activities, such as arabinofuranosidase and acetyl esterase, were also detected, suggesting the adaptation of the bacterium studied to nixtamal dough. It was concluded that Streptococcus infantarius 25124 isolated from pozol was able to use arabinoxylans, which are present in nixtamal dough, so fermentation does not depend exclusively on free sugars and starch.